The effect of computer use on the occurrence of migraine - Radmilo, Ljiljana; Cvijanović, Milan (Vojnosanitetski pregled, 2022)
Background/Aim. Risk factors concerning computer use-related migraine onsets are still unknown. The aim of this study was to determine the prevalence of headaches in computer users as well as the effects of computer use and behavior on the prediction of migraine presence. Methods. A cross-sectional study included 1,500 subjects from the general population who were given a questionnaire to assess the presence and type of headache and questions regarding computer-assisted behavior. All examinees were divided into two groups: the first group consisted of respondents who had a headache, and the second group consisted of subjects without a headache. Results. A total of 67.9% of the subjects had a headache, of which 23.9% had a migraine. Results of multinomial regression analysis showed that significant predictors of the migraine group, compared to the group without headache, were gender (female) and family anamnesis positive for migraine, as well as spending more time on the computer, making shorter and infrequent breaks in which physical activities were less included. Furthermore, members of the migraine group, compared with the group with other types of headaches, were younger and had family anamnesis, rarely made pauses during computer use, and their pauses were shorter. Conclusion. Improper and excessive computer use could be considered a risk factor for migraine occurrence, particularly in young people who have positive family anamnesis for migraine.